Design and Analysis of Low Pole Variable Flux Reluctance Machine - Hilmi Gurleyen (IEEE Access)
This paper presents a comprehensive analytical model that reveals the detailed harmonic structure of flux linkage in the armature windings of a 6-slot/4-pole variable flux reluctance machine (VFRM). By integrating armature winding, field winding, and permeance functions, the model accurately characterizes the complex harmonic profile arising from the double-slot structure, which induces a modulation effect. In particular, even-order harmonics dominate the harmonic spectrum, contributing to a significant torque ripple. To address this issue, this paper proposes a novel dual-stator VFRM design, featuring reverse-direction armature windings for the front and rear stators, aimed at eliminating even-order harmonics. The proposed configuration successfully eliminates even-order harmonics, as confirmed through analytical modeling and experimental validation on a prototype machine. The results show a significant reduction in torque ripple. Furthermore, while traditional VFRM topologies with high pole combinations are typically limited by core losses at high speeds, the proposed design mitigates this constraint, providing enhanced performance across a wider range of operating conditions.